2005
DOI: 10.3354/meps295135
|View full text |Cite
|
Sign up to set email alerts
|

Effects of starvation, ammonium concentration, and photosynthesis on the UV-dependent accumulation of mycosporine-like amino acids (MAAs) in the coral Stylophora pistillata

Abstract: This study addresses several unresolved questions regarding the biosynthesis, metabolism, regulation, and diversity of MAAs in zooxanthellate scleractinian corals. Starved colonies of Stylophora pistillata accumulated the same concentrations of mycosporine-like amino acids (MAAs) as fed corals after 28 d of exposure to photosynthetically available radiation (PAR) and ultraviolet radiation (UVR), suggesting that dietary MAAs are of little quantitative importance in this phototrophic symbiosis. Starved corals co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 51 publications
0
24
0
Order By: Relevance
“…Host starvation is thought to reduce ammonium assimilation in the zooxanthellae as well as photosynthetic rates, and has been shown to increase cell degradation and reduce cell division and numbers (Fitt and Cook 2001;Titlyanov et al 2000Titlyanov et al , 2001. Corals typically maintain high levels of lipids derived from excess photosynthetically Wxed carbon and receive substantial amounts of essential fatty acids (Harland et al 1993), amino acids (Wang and Douglas 1999) and mycosporine-like amino acids (Shick et al 2005) from their zooxanthellae. In addition, the coral host is believed to obtain essential nutrients for tissue synthesis from heterotrophic sources (Dubinsky and Jokiel 1994;Mueller-Parker et al 1994;Anthony et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Host starvation is thought to reduce ammonium assimilation in the zooxanthellae as well as photosynthetic rates, and has been shown to increase cell degradation and reduce cell division and numbers (Fitt and Cook 2001;Titlyanov et al 2000Titlyanov et al , 2001. Corals typically maintain high levels of lipids derived from excess photosynthetically Wxed carbon and receive substantial amounts of essential fatty acids (Harland et al 1993), amino acids (Wang and Douglas 1999) and mycosporine-like amino acids (Shick et al 2005) from their zooxanthellae. In addition, the coral host is believed to obtain essential nutrients for tissue synthesis from heterotrophic sources (Dubinsky and Jokiel 1994;Mueller-Parker et al 1994;Anthony et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Levels of inorganic and organic nutrients in supplied seawater were low (Ferrier-Pagès et al 2001). After healing, feeding was stopped and nubbins were first maintained 5 wk under controlled conditions before the start of the experiment, to cancel any feeding effect (Grover et al 2002, Shick et al 2005, Rodrigues & Grottoli 2007. The above papers indeed showed that 4 wk after the end of feeding, protein or lipid levels were significantly decreased in the coral tissue, cancelling the feeding effect.…”
Section: Biological Materialsmentioning
confidence: 96%
“…A total of 36 small experimental colonies (nubbins, surface area 5 to 8 cm 2 ) per species, 6 nubbins from each parent colonies, were created prior to the experiment, evenly distributed into 6 glass aquaria (20 litre volume) and allowed to recover for 4 weeks. During the recovery period, nubbins were not provided with food in order to remove any previous feeding effect on their physiology (see Shick et al, 2005). During the experimental period (5 weeks), nubbins in three of the six tanks (18 per species) were provided with Artemia salina nauplii three times a week (feeding density of approximately 2000 prey per nubbin per feeding event) whereas nubbins in the remaining three tanks (18 per species) received no food at all.…”
Section: Study Species and Experimental Treatmentsmentioning
confidence: 99%